2017
DOI: 10.17663/jwr.2017.19.1.037
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Fate of Stormwater Runoff Pollutants in Constructed Wetlands

Abstract: Nonpoint source (NPS) pollution continues to degrade the water quality. NPS pollutants signals high concerns against a sustainable environment. Low impact development (LID) is the leading management practice which regulates and treats stormwater runoff especially in highly impervious urban areas. Constructed wetlands are known to have efficient removal capability of NPS pollutants. Likewise, these LID facilities were intended to maintain the predeveloped hydrologic regime through series of mechanisms such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The removal efficiency of a nature-based stormwater treatment facility varies depending on the influent water quality, filter media characteristics, microbiological activities, and the type of vegetation utilized in the system [34,36]. Iris, commonly planted in CWs, is effective in removing nitrogen in water [37,38]. Iris is capable of simultaneously absorbing nitrous oxide and deoxidizing nitrogen in its roots [12].…”
Section: Implication Of Plant Growth and Chlorophyll Changes In The H...mentioning
confidence: 99%
See 1 more Smart Citation
“…The removal efficiency of a nature-based stormwater treatment facility varies depending on the influent water quality, filter media characteristics, microbiological activities, and the type of vegetation utilized in the system [34,36]. Iris, commonly planted in CWs, is effective in removing nitrogen in water [37,38]. Iris is capable of simultaneously absorbing nitrous oxide and deoxidizing nitrogen in its roots [12].…”
Section: Implication Of Plant Growth and Chlorophyll Changes In The H...mentioning
confidence: 99%
“…biological activities, and the type of vegetation utilized in the system [34,36]. Iris, commonly planted in CWs, is effective in removing nitrogen in water [37,38]. Iris is capable of simultaneously absorbing nitrous oxide and deoxidizing nitrogen in its roots [12].…”
Section: Implication Of Plant Growth and Chlorophyll Changes In The H...mentioning
confidence: 99%
“…SWs are built particularly for purifying SR and commonly have less biodiversity than natural wetlands in terms of both plant and animal life. Alihan et al (2017) assessed the impact of SWs on controlling initial SR pollution on campus. They found suspended solid, total N, total P, and trace metal elimination rates of 60%-72%, 40%-50%, and 30%-80%, respectively.…”
Section: Figure 16mentioning
confidence: 99%
“…It was found that vegetated microcosm wetlands effectively reduced pollutant concentrations in the stormwater by up to 76% [14]. Alihan et al (2017) recommended the use of CWs for treating urban stormwater runoff. The CWs, which treat runoff from impervious roads and parking lots, effectively reduced the total runoff volume and pollutant concentrations by up to 37% and 81%, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Alihan et al (2017) recommended the use of CWs for treating urban stormwater runoff. The CWs, which treat runoff from impervious roads and parking lots, effectively reduced the total runoff volume and pollutant concentrations by up to 37% and 81%, respectively [15]. Studies regarding the applicability of CWs in agricultural runoff treatment were also conducted by several authors.…”
Section: Introductionmentioning
confidence: 99%